2010
DOI: 10.1086/653044
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Compatibility and Choice Conflict

Abstract: For most forms of conscious consumer choice, product attributes serve as the means that consumers use to accomplish their goals. Because there is competition between products in the marketplace, consumption decisions typically present conflict between means to achieve a goal. In this article, we examine the consequences of conflict between regulatory means on consumers' decisions and show that its resolution depends on whether the means-that is, the attributes-are compatible with the consumer's regulatory orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…With heightened engagement, both attraction to (in the case of fit) and repulsion from (in the case of non-fit) a target is magnified (Hong and Lee, 2008). Levav et al (2010) observed that compatibility between participants' regulatory focus and product attributes led to higher engagement in five of the six comparisons.…”
Section: Regulatory Fit and Underlying Mechanisms (Engagement Pu Anmentioning
confidence: 89%
“…With heightened engagement, both attraction to (in the case of fit) and repulsion from (in the case of non-fit) a target is magnified (Hong and Lee, 2008). Levav et al (2010) observed that compatibility between participants' regulatory focus and product attributes led to higher engagement in five of the six comparisons.…”
Section: Regulatory Fit and Underlying Mechanisms (Engagement Pu Anmentioning
confidence: 89%
“…Similarly, performance attributes were more compatible with promotion orientation while reliability attributes were more compatible with prevention orientation. In a similar vein, Levav, Kivetz, and Cho () find that participants associate different product attributes more with promotion‐ or prevention‐orientation and are likely to choose products where attributes are compatible with their regulatory orientation. These findings are consistent with research that suggests that consumers tend to compartmentalize product decisions into promotion‐related or prevention‐related categories.…”
Section: Regulatory Orientation and The Relevance Of Positive And Negmentioning
confidence: 89%
“…For example, environmental concerns regarding food choices will be well received by adventurous consumers, who are the most frequent organic and local shoppers, but not by careless consumers, who are the least likely to buy organic and local foods. In other words, there is motivational compatibility (Levav et al 2010) for adventurous consumers, but not for careless consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of healthiness, safety, convenience, and cost can be classified as prevention focus because the orientation is one of avoidance of harm or expense, e.g. time or money (Levav et al 2010). The ''meal preparation'' variables are worded in terms of aspirations or goals, reflecting a promotion focus, while the ''desired consequences'' are worded as obligations or responsibilities; hence, they reflect a prevention focus.…”
Section: Methodsmentioning
confidence: 99%